Hybrid Cooling System - Rumimelinio, Muhammad Syafiq; Hairul, Muhamad Haikal; Mohamad Fakhrul Radzi; Nor Baizura Hamid (Multidisciplinary Applied Research and Innovation, 2025)
This project aims to develop an innovative hybrid cooling system that combines a Dual-Functional Rainwater Harvesting System that is environmentally friendly and capable of generating natural electrical energy. The main objective of this study is to produce a Hybrid Cooling system that can generate electrical power, identify its capability as an interior and exterior cooler, and determine voltage output to meet high voltage requirements. This study uses rainwater, sunlight, and wind as test parameters to assess the efficiency of water turbines, solar panels, and windmills in generating electrical energy. The tests aim to verify the turbine’s capacity to produce electric currents that can drive fans for room cooling and water pump machines for roof cooling systems during the summer. Materials include turbines, water pumps, sprinklers, inverters, batteries, charge controllers, solar panels, and exhaust fans. Testing involves measuring indoor and outdoor temperatures using an infrared thermometer and voltage output using a multimeter. The study results show that the average indoor temperature after cooling system activation is 26.2°C in the morning, 30.3°C at noon, and 27.1°C at night, while the average external temperature is 26.6°C in the morning, 31.3°C at noon, and 27.1°C at night. Solar panels generate an average of 16V on sunny days, while water turbines generate up to 0.13V during rainfall. In conclusion, this study has successfully produced a system that offers sustainable and environmentally friendly solutions for residences. This system not only meets practical needs but also reflects an innovative approach to integrating renewable energy into everyday life, paving the way for more sustainable and energy-efficient homes.